12‐channel receive array with a volume transmit coil for hand/wrist imaging at 7 T. Issue 1 (13th December 2012) - Raghuraman, Sairamesh; Mueller, Matthias F.; Zbýň, Štefan; Baer, Peter; Breuer, Felix A.; Friedrich, Klaus M.; Trattnig, Siegfried; Lanz, Titus; Jakob, Peter M.
<x xml:space="preserve">Abstract</x> Purpose To develop a coil configuration for high‐resolution imaging of different regions of the hand and wrist at 7 T. Materials and Methods A quadrature bandpass birdcage and a 12‐channel high density receive array were developed for imaging metacarpus and wrist. Workbench and magnetic resonance imaging (MRI) measurements were done to characterize the coil and obtain in vivo images. Electromagnetic simulations were performed to assess the uniformity of transmit profile and calculate the specific absorption rate (SAR). Results The results obtained show that the constructed transmit coil can be used in combination with receive arrays, without the need to retune the same. The developed wrist array was used to produce images of ultrahigh resolution (0.19 × 0.19 × 0.5 mm3), revealing fine anatomical details. Simulations show that a near‐uniform transmit profile is possible throughout the hand. No inhomogeneities were observed in the transmit profile, unlike a human head or abdomen at 7 T, due to the small volume of the hand and its low conductive regions. Conclusion While transceive arrays are usually preferred at 7 T due to issues related to decrease in wavelength, it is shown in this study that with regard to hand‐imaging optimized high‐density receive arrays are a good solution to obtain images of extremely fine resolution of different regions. J. Magn. Reson. Imaging 2013;38:238–244. © 2012 Wiley Periodicals, Inc.